Qrio, the robot that could. - Geppert, L.
A technical marvel, Sony's biped humanoid promises to revolutionize home entertainment.
Keywords: Qrio robot; Sony Corporation; Accelerometer; Biped humanoid robot; Charged-coupled device camera; Home entertainment; Microprocessors; Motor actuators